Ribonucleotide reductase inhibitors suppress SAMHD1 ara‐CTPase activity enhancing cytarabine efficacy - Sean G Rudd; Nikolaos Tsesmetzis; Kumar Sanjiv; Cynthia BJ Paulin; Lakshmi Sandhow; Juliane Kutzner; Ida Hed Myrberg; Sarah S Bunten; Hanna Axelsson; Si Min Zhang; Azita Rasti; Petri Mäkelä; et al. (EMBO Molecular Medicine, 2020)
Abstract The deoxycytidine analogue cytarabine (ara‐C) remains the backbone treatment of acute myeloid leukaemia (AML) as well as other haematological and lymphoid malignancies, but must be combined with other chemotherapeutics to achieve cure. Yet, the underlying mechanism dictating synergistic efficacy of combination chemotherapy remains largely unknown. The dNTPase SAMHD1, which regulates dNTP homoeostasis antagonistically to ribonucleotide reductase (RNR), limits ara‐C efficacy by hydrolysing the active triphosphate metabolite ara‐CTP. Here, we report that clinically used inhibitors of RNR, such as gemcitabine and hydroxyurea, overcome the SAMHD1‐mediated barrier to ara‐C efficacy in primary blasts and mouse models of AML, displaying SAMHD1‐dependent synergy with ara‐C. We present evidence that this is mediated by dNTP pool imbalances leading to allosteric reduction of SAMHD1 ara‐CTPase activity. Thus, SAMHD1 constitutes a novel biomarker for combination therapies of ara‐C and RNR inhibitors with immediate consequences for clinical practice to improve treatment of AML.